Polyamide composite nanofiltration membrane as well as preparation method and application thereof
By using hydrotalcite colloids and piperazine in the nanofiltration membrane to form an intermediate layer and perform interfacial polymerization, the problem of limited performance optimization of polyamide nanofiltration membrane on the nanoscale is solved, and a high-throughput and high retention polyamide composite nanofiltration membrane is achieved, which is suitable for a variety of industrial applications.
Patent Information
- Application Number
- CN202411960847.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The performance optimization of existing polyamide nanofiltration membranes is limited on the nanoscale, which is mainly due to the lack of controllability caused by the diffusion control behavior of amine monomers, which affects the permeability and selectivity of the membrane.
By mixing hydrotalcite colloid with piperazine, a precursor material liquid is formed, and an intermediate layer-porous base film is formed on the porous base film. Then, a phenylatriacetic chloride solution is added dropwise to the intermediate layer side to perform an interfacial polymerization reaction to form a polyamide composite nanofiltration membrane.
The high throughput and high retention rate of polyamide composite nanofiltration membrane is achieved, and it can effectively intercept salt, dye molecules and antibiotic molecules, and is suitable for desalination, wastewater treatment and resource recycling.
Smart Images

Figure CN119607920A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of membrane separation, and in particular to a polyamide composite nanofiltration membrane and a preparation method and application thereof. Background Art
[0002] Membrane separation technology has shown great advantages due to its high efficiency, energy saving and easy intensification. Nanofiltration technology can intercept divalent salts and molecules with a molecular weight of more than 200 Daltons, and is a key means to achieve goals such as water softening, wastewater treatment and resource recovery. Polyamide nanofiltration membranes prepared by interfacial polymerization of amine monomers and acyl chloride monomers at the water-oil interface dominate the market due to their cost-effectiveness and scalability. However, due to the limitations of membrane preparation technology and materials, there is a trade-off between permeability and selectivity. The key lies in the lack of controllability caused by the diffusion-controlled behavior of amine monomers during interfacial polymerization, which hinders the performance optimization of membranes at the nanoscale.
[0003] The strategy of the intermediate layer is an important method to improve membrane performance. In the past decade, a variety of nanomaterials such as cadmium hydroxide nanowires, carbon nanotubes, and graphene oxide have been developed for the preparation of intermediate layers, thereby realizing the preparation of high-performance nanofiltration membranes. Exfoliated hydrotalcite nanosheets are also used as intermediate layer materials. However, the nanofiltration performance of nanofiltration membranes prepared with exfoliated hydrotalcite nanosheets as intermediate layers needs to be further improved, and it is not easy to achieve large-scale preparation. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a polyamide composite nanofiltration membrane and a preparation method and application thereof. The polyamide composite nanofiltration membrane prepared by the preparation method provided by the present invention has excellent nanofiltration performance and is easier to prepare on a large scale.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a polyamide composite nanofiltration membrane, comprising the following steps:
[0007] Mixing a soluble magnesium salt, a soluble aluminum salt, an inorganic base and water to carry out a nucleation reaction to obtain a hydrotalcite precipitate;
[0008] dispersing the hydrotalcite precipitate in water and performing a crystallization reaction to obtain a hydrotalcite colloid;
[0009] Mixing the hydrotalcite colloid and piperazine to obtain a precursor liquid;
[0010] After coating the precursor liquid on the porous base film, film forming is performed to form an intermediate layer-porous base film composite film;
[0011] A trimesoyl chloride solution is dripped onto the middle layer side of the middle layer-porous base membrane composite membrane to carry out an interfacial polymerization reaction, thereby obtaining the polyamide composite nanofiltration membrane.
[0012] Preferably, the soluble magnesium salt includes one or more of magnesium chloride, magnesium nitrate and magnesium sulfate, the soluble aluminum salt includes one or more of aluminum chloride, aluminum nitrate and aluminum sulfate, and the inorganic base includes sodium hydroxide and / or sodium carbonate.
[0013] Preferably, the molar ratio of the soluble magnesium salt to the soluble aluminum salt is 2 to 4:1, and the molar amount of the inorganic base is 2 to 2.1 times the total molar amount of the soluble magnesium salt and the soluble aluminum salt.
[0014] Preferably, the nucleation reaction is carried out in a colloid mill, and the time of the nucleation reaction is 2 to 5 minutes.
[0015] Preferably, the temperature of the crystallization reaction is 60-120° C., and the time is 18-36 hours; and the solid content of the hydrotalcite colloid is 0.1-4 wt %.
[0016] Preferably, in the precursor liquid, the solid content is 0.01-0.8 wt %, and the concentration of piperazine is 0.01-0.2 wt %.
[0017] Preferably, the coating amount of the precursor liquid is 0.1 to 0.5 mL / cm 2 .
[0018] Preferably, the concentration of the trimesoyl chloride solution is 0.05-0.5 wt %, and the time of the interfacial polymerization reaction is 10-20 s.
[0019] The present invention also provides a polyamide composite nanofiltration membrane prepared by the preparation method described in the above technical solution, wherein the polyamide composite nanofiltration membrane comprises a porous base membrane, a hydrotalcite layer coated on the base membrane, and a polyamide layer attached to the hydrotalcite layer.
[0020] The present invention also provides the use of the polyamide composite nanofiltration membrane described in the above technical solution in desalination, wastewater treatment or resource recovery.
[0021] The invention provides a method for preparing a polyamide composite nanofiltration membrane.
[0022] The present invention first prepares hydrotalcite colloid by a nucleation reaction and a crystallization reaction isolation method (i.e., the nucleation reaction and the crystallization reaction are carried out step by step); then, the hydrotalcite colloid is mixed with piperazine, and the obtained precursor liquid is coated on a porous base film to form a hydrotalcite intermediate layer containing piperazine molecules; further, a trimesoyl chloride solution is dripped onto the surface of the intermediate layer, and an interfacial polymerization reaction occurs to form a polyamide layer, and finally a polyamide composite nanofiltration membrane is prepared.
[0023] The present invention uses hydrotalcite colloid, and compared with the prior art that directly uses peeled hydrotalcite nanosheets, the obtained intermediate layer is rougher and has a higher specific surface area, so that the flux of the polyamide composite nanofiltration membrane is higher. At the same time, the polyamide nanofiltration membrane is the most widely used nanofiltration membrane in commercial applications. However, due to the limitations of the membrane preparation method and materials, the performance improvement of the membrane is limited. The applicant found that this is because the interfacial polymerization reaction is a reaction controlled by the diffusion of the amine monomer. However, in the traditional preparation method of the polyamide nanofiltration membrane, the amine monomer is directly loaded on the porous base membrane, and then the acyl chloride monomer is added to perform interfacial polymerization to form a polyamide layer; in the above preparation method, the amine monomer is in a free state and the diffusion is uncontrollable, resulting in the uncontrollability of the polyamide layer, and it is impossible to prepare a higher performance membrane, especially the flux. The present invention deposits a precursor liquid containing hydrotalcite colloid and piperazine on a porous base film, and the hydrogen bond interaction between the uniformly distributed hydroxyl groups of the hydrotalcite main layer and the amine monomer (piperazine) and the blocking diffusion of the amine monomer (piperazine) by the two-dimensional layer can realize the controllable diffusion of the amine monomer, thereby preparing an ultra-thin, higher-performance polyamide layer, so that the final polyamide composite nanofiltration membrane has excellent flux. In addition, the preparation method of the present invention mixes the hydrotalcite colloid and the amine monomer (piperazine) and then applies them on the porous base film. Compared with the prior art, the intermediate layer and the adsorbed amine monomer are separately coated, and the scouring of the intermediate layer by the adsorbed amine monomer process is avoided, so that the success rate of film preparation is higher; and the two-step one-step operation is simpler, and it is easy to scale and industrialize.
[0024] The data of the examples show that the polyamide composite nanofiltration membrane provided by the present invention has excellent nanofiltration performance, that is, it has a high retention rate for salt (especially sodium sulfate and magnesium sulfate), dye molecules (methyl blue) and antibiotic molecules (clindamycin phosphate and bacitracin) while having a high flux, so that the polyamide composite nanofiltration membrane has the potential to be used in desalination (especially antibiotic desalination), wastewater treatment or resource recovery. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the XRD pattern of the hydrotalcite colloid obtained in Example 1;
[0026] Figure 2 This is a SEM image of the middle layer in the middle layer-porous base membrane composite membrane obtained in Example 1;
[0027] Figure 3 This is a planar SEM image of the polyamide composite nanofiltration membrane obtained in Example 1;
[0028] Figure 4 This is a cross-sectional SEM image of the polyamide composite nanofiltration membrane obtained in Example 1;
[0029] Figure 5 The nanofiltration performance of the polyamide composite nanofiltration membrane obtained in Example 1 for different salts. DETAILED DESCRIPTION
[0030] The present invention provides a method for preparing a polyamide composite nanofiltration membrane, comprising the following steps:
[0031] Mixing a soluble magnesium salt, a soluble aluminum salt, an inorganic base and water to carry out a nucleation reaction to obtain a hydrotalcite precipitate;
[0032] dispersing the hydrotalcite precipitate in water and performing a crystallization reaction to obtain a hydrotalcite colloid;
[0033] Mixing the hydrotalcite colloid and piperazine to obtain a precursor liquid;
[0034] After coating the precursor liquid on the porous base film, film forming is performed to form an intermediate layer-porous base film composite film;
[0035] A trimesoyl chloride solution is dripped onto the middle layer side of the middle layer-porous base membrane composite membrane to carry out an interfacial polymerization reaction to obtain the polyamide composite nanofiltration membrane.
[0036] Unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.
[0037] The invention mixes soluble magnesium salt, soluble aluminum salt, inorganic base and water, and performs nucleation reaction to obtain hydrotalcite precipitation.
[0038] In the present invention, the soluble magnesium salt preferably includes one or more of magnesium chloride, magnesium nitrate and magnesium sulfate, and more preferably magnesium chloride. In the present invention, the soluble aluminum salt preferably includes one or more of aluminum chloride, aluminum nitrate and aluminum sulfate, and more preferably aluminum chloride. In the present invention, the inorganic base preferably includes sodium hydroxide and / or sodium carbonate, and more preferably sodium hydroxide. In the present invention, the water is preferably deionized water.
[0039] In the present invention, the molar ratio of the soluble magnesium salt to the soluble aluminum salt is preferably 2 to 4: 1, specifically preferably 2: 1, 2.5: 1, 3: 1, 3.5: 1 or 4: 1. In the present invention, the molar amount of the inorganic base is preferably 2 to 2.1 times the total molar amount of the soluble magnesium salt and the soluble aluminum salt, and more preferably 2 times the total molar amount of the soluble magnesium salt and the soluble aluminum salt.
[0040] In the present invention, the nucleation reaction is preferably carried out in a colloid mill, and the rotation speed of the colloid mill is preferably 2000-3000 rpm. In the present invention, the time of the nucleation reaction is preferably 2-5 min, and more preferably 2 min, 3 min, 4 min or 5 min.
[0041] In the present invention, the mixing of soluble magnesium salt, soluble aluminum salt, inorganic base and water to carry out a nucleation reaction preferably includes the following steps: dissolving soluble magnesium salt and soluble aluminum salt in water to obtain a mixed salt solution; dissolving inorganic base in water to obtain an inorganic base solution; adding the mixed salt solution and the inorganic base solution to a colloid mill at the same time to carry out a nucleation reaction. In the present invention, in the mixed salt solution, the concentration of soluble magnesium salt is preferably 0.2-0.3 mol / L, and the concentration of soluble aluminum salt is preferably 0.1-0.15 mol / L. In the present invention, the concentration of the inorganic base solution is preferably 0.3-0.45 mol / L
[0042] After the nucleation reaction, the present invention preferably further comprises: centrifuging the obtained nucleation reaction liquid, collecting the precipitate, and washing the precipitate to obtain the hydrotalcite precipitate. In the present invention, the washing agent is preferably water, the water is preferably deionized water, and the number of washing times is preferably 3 times.
[0043] After obtaining the hydrotalcite precipitate, the present invention disperses the hydrotalcite precipitate in water to perform a crystallization reaction to obtain a hydrotalcite colloid.
[0044] In the present invention, the temperature of the crystallization reaction is preferably 60-120°C, and more preferably 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C; the time is preferably 18-36h, and more preferably 24h. In the present invention, the solid content of the hydrotalcite colloid is preferably 0.1-4wt%, and more preferably 1wt%. In the present invention, the crystallization reaction is preferably carried out under closed conditions.
[0045] In a specific embodiment of the present invention, dispersing the hydrotalcite precipitate in water and performing a crystallization reaction preferably comprises the following steps: dispersing the hydrotalcite precipitate in water, adding the hydrotalcite precipitate into a reactor, sealing the reactor, and placing the reactor in an oven for crystallization reaction. In the present invention, the reactor is preferably a polytetrafluoroethylene reactor.
[0046] In the present invention, the hydrotalcite colloid is preferably stored in a sealed container when not in use.
[0047] In the present invention, the solid phase component of the hydrotalcite colloid is hydrotalcite (LDH), the hydrotalcite is a magnesium aluminum layered double hydroxide, and the interlayer anion of the magnesium aluminum layered double hydroxide is CO3 2- , that is, the solid phase component of the hydrotalcite colloid is the interlayer anion CO3 2- The present invention uses hydrotalcite colloid, and compared with the prior art that directly uses peeled hydrotalcite nanosheets, the obtained intermediate layer is rougher and has a higher specific surface area, so that the polyamide composite nanofiltration membrane has a higher flux.
[0048] After obtaining the hydrotalcite colloid, the present invention mixes the hydrotalcite colloid with piperazine to obtain a precursor liquid.
[0049] In the present invention, the solid content of the precursor solution is preferably 0.01 to 0.8 wt %, and the concentration of piperazine is preferably 0.01 to 0.2 wt %.
[0050] In a specific embodiment of the present invention, mixing the hydrotalcite colloid and piperazine to obtain a precursor liquid preferably includes the following steps: mixing the hydrotalcite colloid and piperazine to obtain a piperazine-hydrotalcite mixture; diluting the piperazine-hydrotalcite mixture to obtain the precursor liquid; the dilution reagent is preferably water, and the dilution multiple is preferably 5 to 10 times.
[0051] After the precursor liquid is obtained, the present invention applies the precursor liquid to the porous base membrane and then forms a film to form an intermediate layer-porous base membrane composite membrane.
[0052] In the present invention, the material of the porous base membrane is preferably nylon. In the present invention, the pore size of the porous base membrane is preferably 0.22 μm. In a specific embodiment of the present invention, the shape of the porous base membrane is preferably circular, and the radius of the circle is preferably 1 to 2 cm, and more preferably 2 cm.
[0053] In the present invention, the coating amount of the precursor liquid is preferably 0.1 to 0.5 mL / cm 2 , preferably 0.16 mL / cm 2 or 0.24 mL / cm 2 In a specific embodiment of the present invention, 2 to 3 mL of the precursor solution is preferably coated on a circular porous base membrane with a radius of 2 cm.
[0054] In the present invention, the film forming method preferably includes standing or filtering. In the present invention, the standing time is preferably 1 min to 3 min, and more preferably 1 min, 1.5 min, 2 min, 2.5 min or 3 min.
[0055] The present invention deposits a precursor liquid containing hydrotalcite colloid and piperazine onto a porous base film, and the hydrogen bond interaction between the evenly distributed hydroxyl groups of the main hydrotalcite layer and the amine monomer (piperazine) and the blocking diffusion of the amine monomer (piperazine) by the two-dimensional layer of the hydrotalcite can realize the controllable diffusion of the amine monomer, thereby preparing an ultra-thin, higher-performance polyamide layer, so that the final polyamide composite nanofiltration membrane has excellent flux and retention rate. In addition, the preparation method of the present invention mixes the hydrotalcite colloid and the amine monomer (piperazine) and then applies them together on the porous base film. Compared with the prior art, the intermediate layer and the adsorption of the amine monomer are separately applied, and the scouring of the intermediate layer during the adsorption of the amine monomer is avoided, so that the success rate of membrane preparation is higher; and the two-step one-step operation is simpler, and it is easy to scale and industrialize.
[0056] After forming the intermediate layer-porous base membrane composite membrane, the present invention drips a trimesoyl chloride solution on the intermediate layer side of the intermediate layer-porous base membrane composite membrane to carry out an interfacial polymerization reaction to obtain the polyamide composite nanofiltration membrane.
[0057] In the present invention, the concentration of the trimesoyl chloride solution is preferably 0.05-0.5 wt%, and more preferably 0.05 wt% or 0.1 wt%. In the present invention, the solvent of the trimesoyl chloride solution is preferably n-hexane.
[0058] In the present invention, the amount of the trimesoyl chloride solution added is preferably enough to completely cover the intermediate layer-porous base membrane composite membrane.
[0059] In the present invention, the temperature of the interfacial polymerization is preferably room temperature, and the time is preferably 10 to 20 seconds.
[0060] After the interfacial polymerization reaction, the present invention preferably further comprises: removing residual liquid with an air knife, and then cleaning the membrane surface with n-hexane to remove excess trimesoyl chloride.
[0061] In the present invention, the polyamide composite nanofiltration membrane is preferably stored in deionized water when not in use.
[0062] In the present invention, piperazine and trimesoyl chloride undergo polymerization reaction at the interface of the intermediate layer to form a polyamide layer.
[0063] The present invention also provides a polyamide composite nanofiltration membrane prepared by the preparation method described in the above technical solution, wherein the polyamide composite nanofiltration membrane comprises a porous base membrane, a hydrotalcite layer coated on the base membrane, and a polyamide layer attached to the hydrotalcite layer.
[0064] In the present invention, the thickness of the intermediate layer is preferably 0.5 μm to 2 μm.
[0065] In the present invention, the thickness of the polyamide layer is preferably 8 to 15 nm.
[0066] The present invention also provides the use of the polyamide composite nanofiltration membrane described in the above technical solution in desalination, wastewater treatment or resource recovery.
[0067] In the present invention, the desalination is preferably antibiotic desalination.
[0068] The present invention does not specifically limit the application of the polyamide composite nanofiltration membrane, and operations familiar to those skilled in the art may be used.
[0069] The polyamide composite nanofiltration membrane provided by the present invention has excellent nanofiltration performance, that is, it has a high retention rate for salt (especially sodium sulfate and magnesium sulfate), dye molecules (methyl blue) and antibiotic molecules (clindamycin phosphate and bacitracin) under the condition of high flux. Based on the high retention rate of the polyamide composite nanofiltration membrane for antibiotic molecules, it has the potential to be applied to desalination, especially antibiotic desalination. Based on the high retention rate of the polyamide composite nanofiltration membrane for salt, it can be used for wastewater treatment. Based on the high retention rate of the polyamide composite nanofiltration membrane for salt, dye molecules and antibiotic molecules, it can achieve the enrichment of the above substances and realize resource recovery.
[0070] The polyamide composite nanofiltration membrane provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0071] Example 1
[0072] (1) Magnesium chloride and aluminum chloride are dissolved in 200 mL of deionized water at a molar ratio of 2:1 to obtain a mixed salt solution, wherein the concentration of magnesium chloride is 0.2 mol / L and the concentration of aluminum chloride is 0.1 mol / L. At the same time, sodium hydroxide is dissolved in 400 mL of deionized water to obtain a sodium hydroxide solution with a concentration of 0.3 mol / L. 200 mL of the mixed salt solution and 400 mL of the sodium hydroxide solution are simultaneously poured into a colloid mill, stirred at 3000 rpm for 3 min, and then a sample is collected, the sample is centrifuged, and a precipitate is collected and repeatedly washed 3 times to obtain a hydrotalcite precipitate.
[0073] (2) Re-dispersing the hydrotalcite precipitate in water, placing the dispersion in a polytetrafluoroethylene reactor, sealing the polytetrafluoroethylene reactor, and placing it in a 100° C. oven for crystallization reaction for 24 hours to obtain a hydrotalcite colloid (solid content of 1 wt%), and storing the hydrotalcite colloid in a sealed container.
[0074] (3) dissolving piperazine in a hydrotalcite colloid having a solid content of 1 wt% to obtain a piperazine-hydrotalcite mixture, wherein the piperazine concentration is 0.5 wt%; diluting the piperazine-hydrotalcite mixture 10 times to obtain a precursor solution (wherein the piperazine concentration is 0.05 wt% and the solid content is 0.1 wt%); and evenly coating 2 mL of the precursor solution on a circular nylon porous filter membrane (pore size 0.22 μm) with a radius of 2 cm, and letting it stand for 1 min to filter the water in the precursor solution to form an intermediate layer-porous base membrane composite membrane.
[0075] (4) Then, a 0.05 wt% solution of trimesoyl chloride (solvent: n-hexane) was dripped onto the middle layer side of the middle layer-porous base membrane composite membrane, so that the trimesoyl chloride solution completely covered the surface of the middle layer-porous base membrane composite membrane, and the interfacial polymerization reaction was carried out for 10 seconds.
[0076] (4) After the interfacial polymerization reaction is completed, the residual liquid is removed by an air knife, and then the membrane surface is cleaned with n-hexane to remove excess trimesoyl chloride to obtain a polyamide composite nanofiltration membrane, and the polyamide composite nanofiltration membrane is stored in deionized water for use.
[0077] Example 2
[0078] (1) Magnesium chloride and aluminum chloride are dissolved in 200 mL of deionized water at a molar ratio of 2:1 to obtain a mixed salt solution, wherein the concentration of magnesium chloride is 0.3 mol / L and the concentration of aluminum chloride is 0.15 mol / L. At the same time, sodium hydroxide is dissolved in 400 mL of deionized water to obtain a sodium hydroxide solution with a concentration of 0.45 mol / L. 200 mL of the mixed salt solution and 4000 mL of the sodium hydroxide solution are simultaneously poured into a colloid mill, stirred at 3000 rpm for 3 min, and then a sample is collected, the sample is centrifuged, and a precipitate is collected and repeatedly washed 3 times to obtain a hydrotalcite precipitate.
[0079] (2) Re-dispersing the hydrotalcite precipitate in water, placing the dispersion in a polytetrafluoroethylene reactor, sealing the polytetrafluoroethylene reactor, and placing it in a 100° C. oven for crystallization reaction for 24 hours to obtain a hydrotalcite colloid (solid content of 1 wt%), and storing the hydrotalcite colloid in a sealed container.
[0080] (3) dissolving piperazine in a hydrotalcite colloid having a solid content of 1 wt% to obtain a piperazine-hydrotalcite mixture, wherein the piperazine concentration is 0.75 wt%; diluting the piperazine-hydrotalcite mixture 10 times to obtain a precursor solution (wherein the piperazine concentration is 0.075 wt% and the solid content is 0.1 wt%); and evenly coating 3 mL of the precursor solution on a circular nylon porous filter membrane (pore size 0.22 μm) with a radius of 2 cm, and letting it stand for 1.5 min to filter the water in the precursor solution to form an intermediate layer-porous base membrane composite membrane.
[0081] (4) Then, a 0.1 wt% solution of trimesoyl chloride (solvent: n-hexane) was dripped onto the middle layer side of the middle layer-porous base membrane composite membrane, so that the trimesoyl chloride solution completely covered the surface of the middle layer-porous base membrane composite membrane, and an interfacial polymerization reaction was carried out for 20 seconds.
[0082] (5) After the interfacial polymerization reaction is completed, the residual liquid is removed by using an air knife, and then the membrane surface is cleaned with an n-hexane solution to remove excess trimesoyl chloride to obtain a polyamide composite nanofiltration membrane; and the interfacial polymerization reaction is stored in deionized water for use.
[0083] Example 3
[0084] (1) Magnesium chloride and aluminum chloride are dissolved in 200 mL of deionized water at a molar ratio of 2:1 to obtain a mixed salt solution, wherein the concentration of magnesium chloride is 0.2 mol / L and the concentration of aluminum chloride is 0.1 mol / L. At the same time, sodium hydroxide is dissolved in 400 mL of deionized water to obtain a sodium hydroxide solution with a concentration of 0.3 mol / L. 200 mL of the mixed salt solution and 400 mL of the sodium hydroxide solution are simultaneously poured into a colloid mill, stirred at 3000 rpm for 3 min, and then a sample is collected, the sample is centrifuged, and a precipitate is collected and repeatedly washed 3 times to obtain a hydrotalcite precipitate.
[0085] (2) Re-dispersing the hydrotalcite precipitate in water, placing the dispersion in a polytetrafluoroethylene reactor, sealing the polytetrafluoroethylene reactor, and placing it in a 100° C. oven for crystallization reaction for 24 hours to obtain a hydrotalcite colloid (solid content of 1 wt%), and storing the hydrotalcite colloid in a sealed container.
[0086] (3) dissolving piperazine in hydrotalcite colloid with a solid content of 1 wt% to obtain a piperazine-hydrotalcite mixture, wherein the piperazine concentration is 1 wt%. The piperazine-hydrotalcite mixture is diluted 5 times to obtain a precursor solution (wherein the piperazine concentration is 0.2 wt% and the solid content is 0.2 wt%); 2 mL of the precursor solution is evenly coated on a circular nylon porous filter membrane (pore size 0.22 μm) with a radius of 2 cm, and allowed to stand for 2 minutes to filter the water in the precursor solution to form an intermediate layer-porous base membrane composite membrane.
[0087] (4) Then, a 0.05 wt% solution of trimesoyl chloride (solvent: n-hexane) was dripped onto the middle layer side of the middle layer-porous base membrane composite membrane, so that the trimesoyl chloride solution completely covered the surface of the middle layer-porous base membrane composite membrane, and the interfacial polymerization reaction was carried out for 10 seconds.
[0088] (5) After the interfacial polymerization reaction is completed, the residual liquid is removed by an air knife, and then the membrane surface is cleaned with an n-hexane solution to remove excess trimesoyl chloride to obtain a polyamide composite nanofiltration membrane, which is then stored in deionized water for future use.
[0089] Comparative Example 1
[0090] The difference from Example 1 is that steps (1) and (2) are omitted.
[0091] (3) Prepare a 0.05 wt % piperazine aqueous solution, then evenly apply 2 mL of the 0.05 wt % piperazine aqueous solution on the surface of the porous base membrane and let it stand for 1 min to remove excess water from the surface of the porous base membrane.
[0092] Steps (4) and (5) are the same as in Example 1.
[0093] Comparative Example 2
[0094] The difference from Example 1 is that steps (1) and (2) are omitted.
[0095] The peeled hydrotalcite nanosheets are obtained, and the peeled hydrotalcite nanosheets are dispersed in water to obtain a 0.1wt% peeled hydrotalcite nanosheet dispersion; piperazine is dissolved in water to form a 0.05wt% piperazine solution; 2mL of the peeled hydrotalcite nanosheet dispersion is evenly coated on a circular nylon porous filter membrane (pore size 0.22μm) with a radius of 2cm, and the membrane is allowed to stand for 2min to filter water in the peeled hydrotalcite nanosheet dispersion to form an intermediate layer-porous basement membrane composite membrane; then 2mL of the 0.05wt% piperazine solution is evenly coated on one side of the intermediate layer of the intermediate layer-porous basement membrane composite membrane, and the membrane is allowed to stand for 2min to filter water in the piperazine solution to form a piperazine-intermediate layer-porous basement membrane composite membrane.
[0096] Steps (4) and (5) are the same as in Example 1.
[0097] Comparative Example 3
[0098] The difference from Comparative Example 2 is that the exfoliated hydrotalcite nanosheets are replaced with exfoliated graphene oxide nanosheets, and the other operations are the same as Comparative Example 2.
[0099] Figure 1 The XRD diagram of the hydrotalcite colloid obtained in Example 1, wherein the abscissa is 2Theta, in degrees, and the ordinate is intensity. Figure 1 It can be seen that the peak position of the XRD spectrum is a typical hydrotalcite (LDH) whose interlayer anion is carbonate. This is because the carbon dioxide in the air will dissolve in water, and the carbonate has the strongest affinity with LDH, so the interlayer ion is carbonate.
[0100] Figure 2 The SEM image of the intermediate layer in the intermediate layer-porous base film composite membrane obtained in Example 1 is shown in FIG. Figure 2 It can be seen that the surface of the Long porous filter membrane has been completely covered by hydrotalcite nanosheets, and the thickness of the hydrotalcite middle layer is 1 μm.
[0101] Figure 3 This is a planar SEM image of the polyamide composite nanofiltration membrane obtained in Example 1. Figure 3 It can be seen that a polyamide layer is prepared by interfacial polymerization on the surface of LDH, and the polyamide layer completely covers the LDH nanosheets and reflects the morphology of the bottom LDH.
[0102] Figure 4 This is a cross-sectional SEM image of the polyamide composite nanofiltration membrane obtained in Example 1. Figure 4 It can be seen that the polyamide layer above the LDH middle layer shows an ultra-thin thickness of only about 10 nm.
[0103] The polyamide composite nanofiltration membranes prepared in the examples and comparative examples were clamped on a cross-flow filtration membrane pool to carry out a nanofiltration performance test.
[0104] Four salts, 1000ppm sodium sulfate (Na2SO4), magnesium sulfate (Mg2SO4), magnesium chloride (MgCl2) and sodium chloride (NaCl), and 40ppm aqueous solutions of methyl blue, clindamycin phosphate and bacitracin were selected as raw materials to evaluate the nanofiltration performance of the membrane. The permeability of the membrane is calculated by the volume of filtrate collected per unit time, expressed as flux, and the calculation formula is as follows:
[0105]
[0106] In formula 1, P is the flux, the unit is L / m 2 ·h·bar; V is the volume of the filtrate, in L; M is the effective area of the membrane, in m 2 ; H is the filtration time, unit is h; ΔP is the pressure difference on both sides of the membrane, unit is bar.
[0107] The retention performance of the membrane is calculated by the change in the concentration of the filtrate and the raw liquid, and is expressed by the retention rate (R). The calculation formula is as follows:
[0108]
[0109] In formula 2, R is the interception rate, in %; C f and C p are the concentrations of the raw material solution and the filtrate salt solution, respectively.
[0110] The results are shown in Table 1 and Figure 5 shown.
[0111] Table 1 Nanofiltration performance of polyamide composite nanofiltration membranes prepared in Examples and Comparative Examples
[0112]
[0113]
[0114] Figure 5 The nanofiltration performance of the polyamide composite nanofiltration membrane obtained in Example 1 for different salts is shown in Table 1. Figure 5 It can be seen that the polyamide composite nanofiltration membrane obtained in Example 1 has a sodium sulfate rejection rate of 95.7% while maintaining excellent permeability with a flux of 75.42 L / m 2 ·h·bar.
[0115] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a polyamide composite nanofiltration membrane, characterized in that: The following steps are involved: Mixing a soluble magnesium salt, a soluble aluminum salt, an inorganic base and water to carry out a nucleation reaction to obtain a hydrotalcite precipitate; dispersing the hydrotalcite precipitate in water and performing a crystallization reaction to obtain a hydrotalcite colloid; Mixing the hydrotalcite colloid and piperazine to obtain a precursor liquid; After coating the precursor liquid on the porous base film, film forming is performed to form an intermediate layer-porous base film composite film; A trimesoyl chloride solution is dripped onto the middle layer side of the middle layer-porous base membrane composite membrane to carry out an interfacial polymerization reaction to obtain the polyamide composite nanofiltration membrane.
2. The preparation method according to claim 1, characterized in that: The soluble magnesium salt includes one or more of magnesium chloride, magnesium nitrate and magnesium sulfate, the soluble aluminum salt includes one or more of aluminum chloride, aluminum nitrate and aluminum sulfate, and the inorganic base includes sodium hydroxide and / or sodium carbonate.
3. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of the soluble magnesium salt to the soluble aluminum salt is 2 to 4:1, and the molar amount of the inorganic base is 2 to 2.1 times the total molar amount of the soluble magnesium salt and the soluble aluminum salt.
4. The preparation method according to claim 1, characterized in that: The nucleation reaction is carried out in a colloid mill, and the time of the nucleation reaction is 2 to 5 minutes.
5. The preparation method according to claim 1, characterized in that: The temperature of the crystallization reaction is 60-120° C., and the time is 18-36 hours; the solid content of the hydrotalcite colloid is 0.1-4wt%.
6. The preparation method according to claim 1, characterized in that: In the precursor liquid, the solid content is 0.01-0.8 wt %, and the concentration of piperazine is 0.01-0.2 wt %.
7. The preparation method according to claim 6, characterized in that: The coating amount of the precursor liquid is 0.1-0.5 mL / cm 2 .
8. The preparation method according to claim 1, characterized in that: The concentration of the trimesoyl chloride solution is 0.05-0.5 wt %, and the time of the interfacial polymerization reaction is 10-20 s.
9. The polyamide composite nanofiltration membrane obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The polyamide composite nanofiltration membrane comprises a porous base membrane, a hydrotalcite layer coated on the base membrane, and a polyamide layer attached to the hydrotalcite layer.
10. Use of the polyamide composite nanofiltration membrane according to claim 9 in desalination, wastewater treatment or resource recovery.
Citation Information
Patent Citations
Reverse osmosis composite membrane containing layered nanometer clay
CN104959048A
Gas-barrier and ionic-conduction bifunctional thin-film material and preparation method thereof
CN107666003A
A modified thin-film composite (TFC) membrane and a method for producing thereof
WO2024096817A1